The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/aud.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Generated Noise on Estimates of Detection Threshold in Quiet for School-Age Children and Adults

Abstract: Objectives Detection thresholds in quiet become adult-like earlier in childhood for high than low frequencies. When adults listen for sounds near threshold, they tend to engage in behaviors that reduce physiologic noise (e.g., quiet breathing), which is predominantly low frequency. Children may not suppress self-generated noise to the same extent as adults, such that low-frequency self-generated noise elevates thresholds in the associated frequency regions. This possibility was evaluated by measuring noise lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We would like to know whether AT is completely determined in quiet by the noise floor, N c false( Q false) false( f false), or whether some other factor is also involved. Buss et al (2016) reported that the distribution of internal “self-generated noise” of NH listeners is similar to the 0-dB HL function (ANSI_S3.6-2010, 2010) on a dB scale as shown in Figure 2(a). If we assume that the distribution of the noise floor, N c false( Q false) false( f false), is indeed the 0-dB HL function, L H L 0 false( f false), it can be formulated as in Equation 15 in Appendix A.…”
Section: Extension Of the Power Spectrum Model Of Maskingmentioning
confidence: 70%
See 1 more Smart Citation
“…We would like to know whether AT is completely determined in quiet by the noise floor, N c false( Q false) false( f false), or whether some other factor is also involved. Buss et al (2016) reported that the distribution of internal “self-generated noise” of NH listeners is similar to the 0-dB HL function (ANSI_S3.6-2010, 2010) on a dB scale as shown in Figure 2(a). If we assume that the distribution of the noise floor, N c false( Q false) false( f false), is indeed the 0-dB HL function, L H L 0 false( f false), it can be formulated as in Equation 15 in Appendix A.…”
Section: Extension Of the Power Spectrum Model Of Maskingmentioning
confidence: 70%
“…(a) Relationship between self-generated noise (Buss et al, 2016) and the HL-0dB function (ANSI_S3.6-2010, 2010) at the ear drum (dashed lines), and at the input to the cochlea (solid lines). (b) The middle ear transfer function, T m i d false( f false) (Glasberg & Moore, 2006) for compensating between them.…”
Section: Extension Of the Power Spectrum Model Of Maskingmentioning
confidence: 99%
“…These nonacoustic responses are likely to involve the tensor tympani (Klockhoff, 1981;Klockhoff & Anderson, 1960). Given diffuse co-activation of the muscles around the ear, this implicates the tensor tympani in both gain control and selective attention-and supports the observed correlation between hearing thresholds and ear canal noise (Buss et al, 2016).…”
Section: As Modulators And/or Sources Of Soundmentioning
confidence: 78%
“…Stekelenburg and Van Boxtel actually suggest that pericranial relaxation is accompanied by relaxation of the middle ear muscles and, given that the basic role of these muscles is to regulate hearing sensitivity (e.g., Borg, 1972), this regulation will in itself lead to lower auditory thresholds. A recent paper (Buss et al., 2016) supports this conclusion by finding that, in a group of tested individuals, lower hearing thresholds were correlated with reduced ear canal noise.…”
Section: The Sound Of Muscles Contractingmentioning
confidence: 84%
“…That is, research has shown that peripheral, within-channel spectral resolution-such as auditory filter width and critical ratio-matures in infancy 16,17 . However, behavioral measures of within-channel spectral resolution (auditory filter width 18 ; on-frequency masking [19][20][21][22][23][24][25] ) and across-channel spectral resolution (spectral ripple discrimination or spectral modulation detection 26,27 ; off-frequency masking 20,22,28 ) in infants and children with normal hearing (NH) are typically poorer than that observed for adult listeners, and do not reach maturation until teenage years [29][30][31][32][33] . This maturational trajectory, however, has not been observed for pediatric CI users 26,29,31,34,35 .…”
mentioning
confidence: 99%